(3GdcGajIs - (3GdeGdcj GdeUQj GdCSfhj, CHh YeQh, GHf GdMGLH, LeGd GdOjf, YKeGf Hf YeQ Hf CHj HcQ, J(B646(3g`s
(3ChdgG (B:s
(3GdcdeI daX hVY deYfi faQO hgjdCfgG EeG Cf JOd Ydi eYfi aj faSgG Ch hGdChd EeG Cf jbJQf HCMO GdCRefI GdKdGKI Ch dG GdKGfj GdGSe hGdChd GdaYd hbO Yde HPdc MO cd hGMO efgGs
(3BNQgG (B:s
(3Ef XgQ aj GddaX jSei daXjG ceG aj GdCeKdI GdePchQI hEf de jXgQ Hd bOQ aj BNQg jSei JbOjQjG fMh CfG GdbGVj hEf de jbOQ aj BNQg jSei eMdjG fMh JhcdfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 211s
(3eYLe GdeDdajf(B: 2 / 366s
(3cTa GdXfhf(B: 2 / 1370s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdfMhs